Excess Body Weight and Incidence of Type 1 and Type 2 Endometrial Cancer: The Norwegian Women and Cancer Study - Sollberger,Tanja Lise; Gavrilyuk,Oxana; Rylander,Charlotta (Clinical Epidemiology, 2020)
Tanja Lise Sollberger,1 Oxana Gavrilyuk,2 Charlotta Rylander3 1Department of Anesthesiology, University Hospital of North Norway, Tromsø, Norway; 2Department of Clinical Oncology, Norwegian Radium Hospital, Oslo, Norway; 3Department of Community Medicine, UiT the Arctic University of Norway, Tromsø, NorwayCorrespondence: Charlotta RylanderDepartment of Community Medicine, UiT the Arctic University of Norway, Tromsø 9037, NorwayTel +47 77644831Email charlotta.rylander@uit.noPurpose: Excess body weight has been associated with increased risk of 13 cancer types and is a particularly strong risk factor for endometrial cancer (EC). Only a few previous studies have assessed the relationship between excess body weight and EC subtypes. In this study, we aimed to investigate the associations between excess weight and incidence of type 1 and type 2 EC.Patients and Methods: We used data from 151,537 participants in the Norwegian Women and Cancer (NOWAC) cohort of which 935 were diagnosed with type 1 and 263 with type 2 EC during follow-up. Height and body weight were self-reported. Multivariable Cox proportional hazard regression was used to assess the associations between body mass index (BMI) and type 1 and type 2 EC.Results: For every 2 kg/m2 increase in BMI, the risk of type 1 EC increased by 21% (HR=1.21, 95% CI: 1.18, 1.24) and the risk of type 2 EC by 10% (HR=1.10, 95% CI: 1.03, 1.16) (pheterogeneity = 0.009). During the period 1991 to 2016, 24.0% (95% CI: 20.0% to 27.8%) of type 1 EC cases was attributable to excess body weight. Avoiding obesity could have prevented 6.6% (95% CI: 3.4% to 9.7%) of type 2 EC cases.Conclusion: Excess body weight was associated with both type 1 and type 2 EC in a dose-dependent manner and the association was significantly stronger in type 1 EC. These findings could support the hypothesis that estrogen plays a more important role in the development of type 1 ECs than in type 2 EC.Keywords: obesity, overweight, cancer of the corpus uteri, uterus cancer, subtypes, body fatness